Collaborative engagement with vector control stakeholders is key to enhance the utility of vector-borne disease models - H. E. Brown; E. Wrench; K. Wolfe; T. C. Moore; J. A. Tangena; L. Sedda (Parasites & Vectors)
Abstract Background Despite the growing complexity, computational power, and mapping capacity incorporated into vector-borne disease models, they still do not fully elucidate the role of environmental, demographic, socioeconomic, or other drivers, and rarely directly inform vector control efforts. To understand how we can improve the utility of vector-borne disease models for vector control activities, we interviewed vector control agents from the United States (USA) and the European Union. Methods Between July and December 2023, in-depth interviews were held using a geographically targeted convenience sample with 26 individuals from organizations involved in vector control operations: 12 in the USA and 14 in the EU. We used both deductive and inductive coding of transcribed interviews to identify themes with the goal of understanding barriers to model use and uptake. Results Despite the recognition that models could be useful, few interviewees reported that models informed surveillance and control activities, citing a mismatch in spatial and temporal scale between model outputs and operational decisions or a general lack of accessibility. Interviewees reported relying on experienced field experts and legacy protocols. Despite these critiques, there is belief that models can support operational decision-making. Conclusions The disconnect between models and users can be improved by allowing time and resources to build collaborative relationships, by acknowledging the knowledge all members bring, and by ensuring clear communication and mutual respect. Modelers must shift their focus by aligning vector-borne disease models with operational needs. Graphical abstract